Plant growth promoting properties of an antarctic strain Amycolatopsis sp. Cq 72-27 - I. Roman; O. Gromyko (Ukrainian Antarctic Journal, 2023)
Unique biotopes can be a source of new plant growth promotion (PGP) bacteria with rare properties. The Antarctic habitat is an attractive location for research, as it is characterized by many stress factors, and the local microbiota is under permanent selective pressure. We believe that the rhizosphere bacteria of this habitat may have important PGP properties that can be used in agriculture. A variety of research methods were used in this work: the molecular genetic technique to establish the gene sequence, chemical to test the ability to produce nitrite, ammonia, and indole acetic acid, microbiological to investigate the cultured properties of the strain, as well as antagonistic and PGP activities. We found that the strain belongs to the genus Amycolatopsis. It showed antagonistic activity against phytopathogenic bacteria (Xanthomonas campestris pv. campestris IMB8003 and Bacillus subtilis ATCC 31324) and fungi (Alternaria alternata DSM 1102, Fusarium oxysporum ІМВ 54201, Aspergillus niger ІМВ 16706), and also demonstrated some PGP properties (solubilization of phosphorus and zinc and production of nitrite and ammonia). Inoculation of wheat seeds with spores of this strain promoted germination and growth of seedlings. The strain has demonstrated properties that make it a promising basis for developing biofertilizers that can be used in agriculture.